Tingkat Kematangan Teknologi Informasi Menggunakan Framework COBIT pada Layanan Teknologi Informasi (Studi Kasus: STIE MDP) - Desy Iba Ricoida (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2015)
Currently a very large role of information technology in all areas of education is no exception, where the roles and appropriate management should be taken to ensure the availability of IT services that support business processes in the organization is on STIE MDP. This study aims to measure the level of maturity (maturity) of the process and information technology services applied to STIE MDP. This study uses a methodology developed COBIT framework for IT Governance Institute (ITGI) for control and auditing of IT with a focus on the domain